European Higher Education and the Internal Market Tensions Between European Policy and National Sovereignty (Issues in Higher Education, 2018)
This book analyses European higher education policies and their three main drivers: the European Commission, the European Court of Justice and the building of the European Higher Education Area through the Bologna Process. Central to the volume is the issue of European institutions' intervention in higher education: building a common area for higher education in a domain protected by subsidiarity is no easy task, and one that must consider the supra-national, national and institutional levels that all play a role in policy implementation. In this volume, the editors and contributors navigate within the tensions between the establishment of an internal market on the one hand and national sovereignty on the other. This volume will surely be of interest and value to those studying and working in the area of higher education policy and understanding relationships between European institutions and member states.